Extended Matrix Variate Hypergeometric Functions and Matrix Variate Distributions - Daya K. Nagar; Raúl Alejandro Morán-Vásquez; Arjun K. Gupta (International Journal of Mathematics and Mathematical Sciences)
Hypergeometric functions of matrix arguments occur frequently in multivariate statistical analysis. In this paper, we define and study extended forms of Gauss and confluent hypergeometric functions of matrix arguments and show that they occur naturally in statistical distribution theory.